Increased yield stability of field-grown winter barley (Hordeum vulgare L.) varietal mixtures through ecological processes. (July 2016) - Creissen, Henry E.; Jorgensen, Tove H.; Brown, James K.M.
Abstract: Crop variety mixtures have the potential to increase yield stability in highly variable and unpredictable environments, yet knowledge of the specific mechanisms underlying enhanced yield stability has been limited. Ecological processes in genetically diverse crops were investigated by conducting field trials with winter barley varieties ( Hordeum vulgare ), grown as monocultures or as three-way mixtures in fungicide treated and untreated plots at three sites. Mixtures achieved yields comparable to the best performing monocultures whilst enhancing yield stability despite being subject to multiple predicted and unpredicted abiotic and biotic stresses including brown rust ( Puccinia hordei ) and lodging. There was compensation through competitive release because the most competitive variety overyielded in mixtures thereby compensating for less competitive varieties. Facilitation was also identified as an important ecological process within mixtures by reducing lodging. This study indicates that crop varietal mixtures have the capacity to stabilise productivity even when environmental conditions and stresses are not predicted in advance. Varietal mixtures provide a means of increasing crop genetic diversity without the need for extensive breeding efforts. They may confer enhanced resilience to environmental stresses and thus be a desirable component of future cropping systems for sustainable arable farming. Highlights: Variety mixtures were less diseased and less prone to lodging than monocultures. Mixtures were more tolerant of unexpected environmental stresses. Yields were more stable in mixtures than monocultures. Mixture success was due to ecological processes: compensation and facilitation. It is possible to fine-tune mixtures to suit specific growing conditions.